Society 5.0: a simulation optimisation study of dynamic scheduling for a grocery store. (23rd March 2022) - Mykoniatis, Konstantinos; Angelopoulou, Anastasia; Nichols, Samira Shirzaei
Society 5.0 refers to a technology-based human-centred society that integrates cyber-physical systems and uses advanced technology to improve everyday life. Queuing systems, such as grocery stores, will transition to Society 5.0. Waiting time in the queue of such systems makes it difficult to determine the necessary number of resources to operate cost-effectively and keep customers satisfied. This work studies a grocery store with two types of resources: cashier-staffed billing counters and self-checkout machines. The objective of the study is to dynamically schedule the required number of resources such that the arriving customers experience reduced waiting times in the queue, while the store maintains low operational costs. The work uses the Simio simulation software and the OptQuest simulation optimisation engine to determine the staffing levels and achieve the aforementioned objectives. The optimisation experiment results showed that using dynamic resource scheduling can assist in maintaining satisfactory customer waiting times and operational costs.